The Effect of Paraphrasing Strategy on the Students’ Ability in Comprehending Narrative Text at the Eighth Grade of SMP Negeri 1 Mandrehe - hidayati, daeli (The Explora, 2023)
Reading is one of English skills that should be mastered by students because through reading, readers get important information, ideas or opinions of text they read about. But the fact, the students of SMP Negeri 1 Mandrehe at the eighth grade in 2015/2016 are not able to get information of narrative text. So, the researcher tries to apply Paraphrasing Strategy to investigate its significant effect on the students’ ability in comprehending narrative text. Paraphrasing Strategy is restating information in reading activity by finding the main ideas of paragraphs and by getting the specific facts of a text in own words. In conducting the research, the research uses quasiexperimental design. The subject of this study is the eighth grade of SMP Negeri 1 Mandrehe in 2015/2016. The population of the research was consists of 103 students, the sample which consists of 68 students by cluster sampling. The data collected both of groups’ pre test, the data were normality and homogenous. The researcher did the treatment to the experimental group by using Paraphrasing Strategy. Based on the result of the data computation, it shown the mean score was 76.61 stated good. In the control group, the researcher taught the students by using conventional mathod. The result of post test was 61.47 stated adequate. Based on the result of hypothesis testing by using t-test, the researcher got tcount ≥ ttable (6.3347 ≥ 1.943 from the ttable with dk = 2(n-1) = 2(34-1) = 66 and the significance level is 5% (∝= 0.05). Because ttableto dk 66 is not be found in the critic distribution t of value table, so ttable is interpolated to dk 60 is 2.000 with ttable to dk 120 is 1.9880 So, ttable = t1/2(dk) = t0.025 x 66 = 1.943. Ha is accepted and H0 is rejected. It can be conclude that there was a significant effect of Paraphrasing Strategy on the students’ ability in comprehending narrative text at the Eighth Grade of SMP Negeri 1 Mandrehe in 2015/2016. Base on the analysis, the researcher suggest to the English teacher to use the strategy to teach the students. The strategy is Paraphrasing Strategy, it can solve the students problems, havefeedback, active and create the relation between teacher and student when teaching readingcomprehension especially in narrative text. Keyword: Students’ Ability in Reading Comprehension, Paraphrasing Strategy